Once Again on ʾbk wdm in Ethiopian Sabaic - Butts, Aaron Michael; Gross, Simcha; Hensley, Michael (Aethiopica, 2022)
In an article published in this journal in 2010, Norbert Nebes argued that ʾbk wdm is an apotropaic formula, which can be translated, for instance in the case of RIÉ 9, as ‘und Waddum ist dein (göttlicher) Vater als Schutz vor einem Widersacher’ (wʾbk wdm [b]n ʿtkm). In contrast, it is proposed here that ʾbk wdm continues the previous list of deity names, as already suggested in 1976 by Roger Schneider. Key to this argument is the distribution of the concluding prepositional phrases bn kl mrʿm, ‘from everyone who is malicious’, and bn ʿtkm, ‘from an adversary’, which only occur in inscriptions that have b-s¹qt, ‘by the protection of’. Thus, the following formula is proposed: b-s¹qt DN(s) bn X, ‘by the protection of divine name(s) from X’.